Cell tropism and viral clearance during SARS-CoV-2 lung infection - Schwab, Constantin; Domke, Lisa Maria; Rose, Fabian; Haußer-Siller, Ingrid; Schirmacher, Peter; Longerich, Thomas (Pathology, research and practice, 2022)
Pulmonary capillary microthrombosis has been proposed as a major pathogenetic factor driving severe COVID-19. Autopsy studies reported endothelialitis but it is under debate if it is caused by SARS-CoV-2 infection of endothelial cells. In this study, RNA in situ hybridization was used to detect viral RNA and to identify the infected cell types in lung tissue of 40 patients with fatal COVID-19. SARS-CoV-2 Spike protein-coding RNA showed a steadily decreasing signal abundance over a period of three weeks. Besides the original virus strain the variants of concern Alpha (B.1.1.7), Delta (B.1.617.2), and Omicron (B.1.1.529) could also be detected by the assay. Viral RNA was mainly detected in alveolar macrophages and pulmonary epithelial cells, while only single virus-positive endothelial cells were observed even in cases with high viral load suggesting that viral infection of endothelial cells is not a key factor for the development of pulmonary capillary microthrombosis.
Gesehen am 17.10.2022